2021
DOI: 10.26714/magnamed.8.1.2021.40-59
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Wound Healing Compounds from Chloroform Extract of Binahong Leaves (Anredera cordifolia (Ten.) Steenis)

Abstract: The leaves of Binahong (Anredera cordifolia (Ten) Steenis) have been widely studied to have benefits and uses in various medical purposes, one of which is in the wound healing process. The existence of several active compounds contained in the leaves of the Binahong tree plant have an important role in wound healing, such as flavonoids, terpenoids, alkaloids, saponins, ascorbic acid and citrate compounds, these compounds are the targeted for further process of this natural product. The eminence of the extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A study revealed the influence of binahong leaf extract on analgesic activity in male mice infused at a dose of 400 mg/Kg BW [12]. The compounds in binahong leaves that might implicate to act as analgesics are flavonoid glycosides, saponins, vitamin C, and flavones [13]. The mechanism of action of flavonoids as analgesics is by inhibiting the enzyme cyclooxygenase (COOX), thereby reducing the production of prostaglandins by arachidonic acid which causes pain.…”
Section: Resultsmentioning
confidence: 99%
“…A study revealed the influence of binahong leaf extract on analgesic activity in male mice infused at a dose of 400 mg/Kg BW [12]. The compounds in binahong leaves that might implicate to act as analgesics are flavonoid glycosides, saponins, vitamin C, and flavones [13]. The mechanism of action of flavonoids as analgesics is by inhibiting the enzyme cyclooxygenase (COOX), thereby reducing the production of prostaglandins by arachidonic acid which causes pain.…”
Section: Resultsmentioning
confidence: 99%
“…17 There are four wound healing phases: the coagulation phase, the inflammatory phase, the proliferation/migration/reepithelialization/ granulation phase, and the remodeling/maturation phase (figure 4). 18,19 In patients with diabetes mellitus, nonhealing/chronic wounds occur; in this condition, the inflammatory phase is prolonged. Diabetic wounds exhibit a persistent inflammatory phase associated with an impediment in forming mature granulation tissue and a reduction in wound tensile strength.…”
Section: Discussionmentioning
confidence: 99%
“…Saponins also stimulate fibroblast proliferation and collagen formation. 26,27 Tannins and alkaloids are antimicrobial and antioxidant, which can prevent and protect the wound area from being damaged by free radicals and inhibit the growth of pathogenic bacteria in the wound.…”
Section: Binahongmentioning
confidence: 99%
“…Binahong leaf alkaloids are antibacterial by interfering with the peptidoglycan component of bacterial cells so that the cell wall layer is not completely formed and cell death occurs. 26,27 Ascorbic acid (vitamin C) functions to increase resistance to infection, maintain mucous membranes, and accelerate wound healing. 28 The use of nanogels in mucosal wound healing shows that CTL nanogel has a significant effect on cell proliferation at various concentrations, its use as a safe and effective drug delivery system.…”
Section: Binahongmentioning
confidence: 99%